Artificial Saliva: Challenges and Future Perspectives for the Treatment of Xerostomia - Łysik, Dawid (Int J Mol Sci, 2019)
The chronic sensation of a dry mouth is a disease condition called xerostomia and affects a large part of the population. Xerostomia is associated with decreased secretion, or more often, qualitative changes in saliva proteins and immunoglobulin concentrations that develop as a result of salivary gland dysfunction. Several reasons causing dry mouth were described, and usually, they include taking medications, diseases or radiotherapy. In some situations, when it is difficult to use salivary stimulants or salivary gland damage is irreversible, the only option might seem to be saliva substitutes. The paper presents the most important aspects considering saliva preparations. The rheological and lubricating properties and the reconstruction of the complex saliva structure has been the main purpose of research. The biological properties of saliva preparations were also widely discussed. As part of the work, the antimicrobial effect of three commercial saliva preparations was tested. Finally, inadequate antimicrobial properties against the strains isolated from the oral cavity were demonstrated. The development of salivary substitutes, in particular, the improvement of antimicrobial properties, can be achieved using nanotechnology, including drug delivery systems containing nanocarriers.